Comparative studies of isolates of colletotrichum gloeosporioides from eighteen Malaysian hosts - S. Kanapathipillai, Vijaya (Universiti Putra Malaysia Press, 1996)
Colletotrichum gloeosporioidesfrom eighteen Malaysian hosts, namely mandarin orange (Citrus reticulata), cacao (Theobroma cacao), an orchid (Cattleya sp.), pepper (Piper nigrum), chilli (Capsicum annum), grass (Imperata cylindrica), mango (Mangifera indica) and legume cover crops (Pueraria phaeseoloides, Centrosema pubescens, and Calopogonium mucunoides) and a weed (Mimosa pudica), vegetables (Psophocarpus tetragonolobus, Phaseolus vulgaris, Vigna radiata, Vigna sesquipedalis and Arachis hypogaea), a shrub (Leucaena leucocephala) and a herbaceous vine (Clitoria ternatea) were examined for colony growth characteristics, morphology of conidia, growth on various media and temperatures and pathogenicity on Phaeseolus bean hypocotyls. Conidium size ofColletotrichum gloeosporioides was 14.25-19.0 x 2.7-5.03 llm. The appressorium size was 6.34-10.08 x 5.28-7.31 llm and the shape was globose/sub-globose/lobed. No correlation between the appressorium size and shape was noticed. The optimum temperature for growth was 28 and 30°C. None of the isolates caused infection symptoms on Phaseolus bean hypocotyls.